Pengaruh Islamic Corporate Governance dan Kecukupan Modal terhadap Nilai Perusahaan yang Dimoderasi oleh Islamic Social Reporting pada Bank Umum Syariah di Indonesia Tahun 2021-2023 - Amelia, Fathiya Rizqy; Sutapa, Sutapa (Universitas Pahlawan Tuanku Tambusai, 2025)
This research aims to examine the impact of Islamic Corporate Governance (ICG) and capital adequacy on firm value, with Islamic Social Reporting (ISR) as a moderating variable in Islamic Commercial Banks in Indonesia during the period 2021–2023. This research uses a quantitative approach with secondary data taken from annual reports and sustainability reports. The sample was determined using the purposive sampling method. The analysis method applied is Moderated Regression Analysis (MRA). The results of the study show that Islamic Corporate Governance significantly and positively affects firm value. On the other hand, firm value is not greatly influenced by capital adequacy. ISR can strengthen the impact of ICG on firm value, but ISR cannot strengthen the relationship between capital adequacy and firm value. These findings indicate that corporate governance based on sharia principles and good Islamic social reporting can increase firm value. This research provides implications for the management of Islamic Commercial Banks to strengthen the implementation of sharia governance principles and improve the quality of social reporting as a strategy to increase investor and stakeholder trust.